O'Reilly software architecture conference, New York, 2018. (O'Reilly Media, 2018)
"This video compilation of O'Reilly's SACON 2018 NY conference stands apart for two reasons: depth and breadth. Depth because it gives you complete freedom to view more than 75 hours of advice on the best approaches to software architecture from over 50 of the world's best software architects, engineers, developer advocates, and designers. Breadth because the topics discussed cover all aspects of software architecture, including often neglected topics such as how to sell your ideas, manage teams, choose technologies wisely, and a host of other soft skills vital to your success as a software architect. A short list of the top speakers you'll hear from includes senior UX designer Abby Beck (Google), solutions architect Sonya Natanzon (Genomic Health), developer advocate Heidi Waterhouse (LaunchDarkly), CEO Ben Evans (jClarity), lead microservices developer Maria Gomez (ThoughtWorks), blockchain expert James Stewart (jystewart.net), CTO Daniel Bryant (SpectoLabs), fast data engineering VP Dean Wampler (Lightbend), and API architecture director Mike Amundsen (CA Technologies)."--Resource description page